The Development of Stage Machinery in the Drottningholm Court Theatre (1764-1766) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The Drottningholm Court Theatre is a prime example of the aesthetic and technical aspirations of courtly spectacle in the second half of the eighteenth century. Its sophisticated stage machinery, based on the innovative vertical capstan and inspired by Central European models, enabled the dramatic space to be transformed with remarkable precision and dynamism. Conceived by Carl Fredrik Adelcrantz under the patronage of Queen Lovisa Ulrika of Prussia, it combined spatial richness with mechanical splendour to create the total theatrical illusion. This integration of architecture, painting, music and movement represents the culmination of Baroque scenography while also anticipating the modernity of artifice. In the contemporary digital landscape, technique has evolved to serve as a conduit for aesthetic expression, seamlessly integrating reality with illusion to create a distinctive experience.
Keywords: Stage machinery; vertical capstan; trompe l’oeil; unique space; interaction between appearance and reality